Cardiovascular vs. non‐cardiovascular deaths after heart failure hospitalization in young, older, and very old patients. (27th November 2022) - Nakamaru, Ryo; Shiraishi, Yasuyuki; Sandhu, Alexander T.; Heidenreich, Paul A.; Shoji, Satoshi; Kohno, Takashi; Takei, Makoto; Nagatomo, Yuji; Nakano, Shintaro; Kohsaka, Shun; Yoshikawa, Tsutomu
Abstract: Aims: The long‐term outcome in patients with heart failure (HF) after hospitalization may vary substantially depending on their age and left ventricular ejection fraction (LVEF). We aimed to assess the relative rates of cardiovascular death (CVD) and non‐CVD based on the age and how the rates differ under the updated LVEF classification system. Methods and results: Consecutively registered hospitalized patients with HF ( N = 3558; 39.7% women with a mean age of 73.9 ± 13.3 years) were followed for a median of 2 (interquartile range, 0.8–3.1) years. The CVDs and non‐CVDs were evaluated based on age [young (<65 years), older (65–84 years), and very old (≥85 years)] and LVEF classification [HF with preserved EF (HFpEF; LVEF ≥50%) and non‐HFpEF (LVEF <50%)]. The adverse clinical events were adjudicated independently by a central committee. Overall, 1505 (42.3%) had HFpEF [young: n = 182 (12.1%), older: n = 894 (59.4%), very old: n = 429 (28.5%)], and 2053 (57.7%) had non‐HFpEF [young: n = 575 (28.0%), older: n = 1159 (56.5%), very old: n = 319 (15.5%)]. During the follow‐up, the crude incidence of all‐cause death was higher in non‐HFpEF than in HFpEF across all age groups (non‐HFpEF vs. HFpEF, young: 10.4% vs. 5.5%, log‐rank P = 0.10; older: 26.6% vs. 20.9%, log‐rank P = 0.002; very old: 36.7% vs. 31.7%, log‐rank P = 0.043). CVDs accounted for more than half of all deaths in non‐HFpEF (young 65.0%, older 64.2%, and very old 55.6%), whereas the proportion of CVDs remained less than half in HFpEF (young 50.0%, older 41.2%, very old 38.2%). HF readmission was associated with subsequent all‐cause death in non‐HFpEF [hazard ratio (HR): 1.72, 95% confidence interval (CI): 1.41–2.09, P < 0.001], but not in HFpEF (HR: 1.12, 95% CI: 0.87–1.43, P = 0.39). Conclusions: The probability of a non‐CVD increases in both LVEF categories with advancing age, but that it is greater in the HFpEF category. The findings indicate that mitigating CV‐related outcomes alone may be insufficient for treating HF in older population, particularly in the HFpEF category.